2009
DOI: 10.3171/2008.4.17492
|View full text |Cite
|
Sign up to set email alerts
|

Antiangiogenic therapy using bevacizumab in recurrent high-grade glioma: impact on local control and patient survival

Abstract: Antiangiogenic therapy using bevacizumab appears to improve survival in patients with recurrent high-grade glioma. A possible change in the invasiveness of the tumor following therapy is worrisome and must be closely monitored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
151
3
10

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 216 publications
(175 citation statements)
references
References 25 publications
10
151
3
10
Order By: Relevance
“…The frequency of distant recurrences in this patient series was 23%. Of note, 20% distant recurrences had been found in an analysis of the recurrence patterns at DRAFT-final first progression of the non-BEV-containing EORTC 26981/22981/NCIC CE.3 trial [23] and prior data suggested a frequency of distant failure of between 20 and 30% with BEV [11,19,20]. Therefore, a controlled analysis should ask the question whether distant recurrences are more frequent in BEV-treated patients versus patients with similar clinical characteristics who have not been exposed to BEV or another antiangiogenic treatment in the observation period.…”
Section: Distant or Diffuse Recurrence May Be A Feature Of Late-stagementioning
confidence: 93%
See 2 more Smart Citations
“…The frequency of distant recurrences in this patient series was 23%. Of note, 20% distant recurrences had been found in an analysis of the recurrence patterns at DRAFT-final first progression of the non-BEV-containing EORTC 26981/22981/NCIC CE.3 trial [23] and prior data suggested a frequency of distant failure of between 20 and 30% with BEV [11,19,20]. Therefore, a controlled analysis should ask the question whether distant recurrences are more frequent in BEV-treated patients versus patients with similar clinical characteristics who have not been exposed to BEV or another antiangiogenic treatment in the observation period.…”
Section: Distant or Diffuse Recurrence May Be A Feature Of Late-stagementioning
confidence: 93%
“…For BEV, various patient series have suggested an increase in diffusely or distantly recurring tumors [11,19]. This gliomatosis-like phenotype or remote spread is best depicted on fluid-attenuated inversion recovery (FLAIR) MRI sequences [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…to evaluate for patterns of recurrence, ie, multifocal or diffuse (or worsening) infiltration on FLAIR sequence. 12,17,24,25 Multifocal recurrence was defined as new sites of contrast-enhanced tumor remote from the original site without an obvious connection observed on FLAIR sequences, whereas diffuse infiltration was defined as the progression of nonenhancing tumor, which lead to Original Article 6.4…”
Section: Assessmentsmentioning
confidence: 99%
“…The activity of bevacizumab alone or in combination with irinotecan for recurrent HGG has been investigated and has produced response rates that range from 35% to 60% and PFS6 rates of 40% to 60% (Table 1). [11][12][13][14][15][16][17][18][19][20][21][22] The current study was a prospective phase 2 trial of single-agent bevacizumab for the treatment of patients with recurrent HGG on an every-3-week schedule to assess PFS, OS, and safety. In addition, outcomes based on VEGFA and VEGFR2 tumor expression were assessed.…”
mentioning
confidence: 99%